Uma avaliação em profundidade da atuação do TCE - CE acerca de auditoria operacional - Freire, Cássio Carvalho Rocha (2024)
This research aims to evaluate the performance of the Court of Auditors of the State of Ceará (TCE - CE), concerning the operational audit carried out by that Court of Auditors, whose objective was to evaluate the adherence of Ceará municipalities to the provisions of the Fiscal Responsibility Law (LRF) especially in relation to its article 11. The aforementioned TCE - CE inspection process was based mainly on the Fiscal Responsibility Law (LRF), thus constituting a central piece in the analysis. This law requires that the entities of the Federation carry out responsible fiscal management, ensuring that revenues are sufficient to cover expenses and that public accounts are balanced. Although it was an important milestone for the control of public finances in Brazil, it is worth noting that the LRF has an excessively fiscal nature, prioritizing budgetary balance over social investments. By imposing strict limits on public spending, the LRF may restrict the investment capacity of government entities, especially in essential areas such as health, education and infrastructure, in addition to hindering the response to economic crises or emergencies. It is therefore necessary to reconcile fiscal responsibility with social responsibility, in order to guarantee quality public services and respond promptly to emergencies and economic crises. In this context, the role of the Audit Courts gains relevance, due to the undeniable potential contribution of these external control bodies to the improvement of public management, especially through operational audits, which are not limited to verifying legal compliance, but also seek to assess the efficiency, effectiveness and efficacy of the public policies implemented. This research used an "in-depth assessment" methodology, based on the model proposed by Lea Rodrigues (2008), and concluded that the actions of the TCE - CE, through the operational audit in question, were aimed at improving municipal public management, with regard to reducing dependence on constitutional transfers and increasing revenue collection capacity, but did not include, in its scope, the social dimension of public spending. It is crucial that the actions of the Courts of Auditors, when monitoring compliance with the LRF, consider, in a more comprehensive manner, the social responsibility associated with fiscal management so that public governance achieves its objectives more broadly and effectively. This implies not only ensuring that public managers follow the LRF rules, but also that they are committed to the well-being of society, seeking a healthy balance between fiscal and social responsibility. In this context, the Courts of Auditors play a fundamental role as agents of change in public management, using operational audits to promote greater efficiency and transparency in the use of public resources. However, it is essential that fiscal responsibility be balanced with social well-being, ensuring that tax collection is directed towards public policies that meet the real needs of the population. Therefore, the TCE - CE, in addition to focusing on compliance with fiscal standards aimed at efficient collection, must also pay attention to the social responsibility of Ceará's municipalities. In other words, the oversight of that Court must not only ensure that Ceará's municipalities are collecting adequately, but also verify whether these resources are being invested in a way that improves the population's quality of life.